Penerapan Model Pembelajaran Kooperatif Tipe JIGSAW Untuk Meningkatkan Aktivitas dan Hasil Belajar Matematika Siswa - Marlinawat Marlinawat; Tina Yunarti (Program Studi Magister Manajemen Pendidikan, 2025)
This Classroom Action Research aimed to improve the participation and academic achievement of students in class XI.F1 at SMAN 1 Gunung Alip in mathematics, particularly on matrix material. The problem arose because conventional teacher-centered teaching methods made students less actively involved in the learning process and resulted in low learning outcomes. Therefore, this study implemented the Jigsaw-type cooperative learning model conducted in two cycles, with each cycle consisting of the stages of planning, action, observation, and reflection. The study involved 31 students of class XI.F1 in the 2023/2024 academic year as the research subjects. The research instruments included student activity observation sheets, learning achievement tests, and field notes. Quantitative data from the tests were analyzed to determine improvements in learning outcomes, while qualitative data from observations were analyzed to describe improvements in student participation. The results of the study showed that the implementation of the Jigsaw-type cooperative learning model successfully improved student engagement and academic achievement. This was indicated by significant improvements across the two cycles conducted. In Cycle I, the level of student participation reached 62.9% with a class mastery percentage of 70.97%. After improving the learning strategy in Cycle II, student activity increased significantly to 70.97%, while the percentage of students achieving mastery rose to 87.10%. These improvements demonstrate that the Jigsaw model can create a more interactive learning environment, encourage collaboration, and foster students’ sense of personal responsibility. In other words, the Jigsaw model proved effective in overcoming passive learning problems and improving both the learning process and mathematics learning outcomes, in line with the objectives of the Merdeka Curriculum.